مساهمة الملتقيات العلمية عبر منصات التعليم الرقمية على جودة البحث العلمي وانعكساتها على الهيئة المنظمة والمتدخلة غبر معاهد التربية البدنية والرياضية - بومدين, حليمة; حجوج, امينة (Institut d’Éducation Physique et Sportive mostaganem 2022/2023, 2023)
The current study aimed to identify the extent of the contribution of scientific forums through digital education platforms to the quality of scientific research and its impact on the organizing body and the stakeholders in some institutes of physical education and sports in Algeria. Positive for the organizing and intervening body in some sports institutes in Algeria. Where the study was carried out on teachers of physical education institutes in Algeria, numbering 50 professors, where the sample was selected in a random manner, and the questionnaire was distributed to them. Descriptive method After collecting the data, processing it statistically, presenting it, and discussing it, the results of the research concluded that the scientific forums through digital education platforms contribute positively to the quality of scientific research and their positive impact on the organizing body and the stakeholders.
LEPS-2023-19
Keywords: Keywords: scientific forums - digital platforms - quality of scientific research / الملقيات العلمية -المنصات الرقمية - جودة البحث العلمي